Spatial analysis shows moderate yet significantly more vigorous crops in AICCRA communities compared to control communities - Song, Chun; Kramer, Berber; Obeng, Faustina; Chepsiror, Calvin; Dalaa, Mustapha; Mahama, Obed; Berti, Lorenzo; Assefa, Thomas; Nowak, Andreea C.; Tepa-Yotto, Ghislian (2025)
In southern Ghana, communities with multiple stakeholder CSA field demonstrations (CSA hubs) show significantly more vigorous crops based on satellite imagery from 2021 to 2025, compared to control communities.